2020
DOI: 10.1073/pnas.2007206117
|View full text |Cite
|
Sign up to set email alerts
|

Thymus-derived B cell clones persist in the circulation after thymectomy in myasthenia gravis

Abstract: Myasthenia gravis (MG) is a neuromuscular, autoimmune disease caused by autoantibodies that target postsynaptic proteins, primarily the acetylcholine receptor (AChR) and inhibit signaling at the neuromuscular junction. The majority of patients under 50 y with AChR autoantibody MG have thymic lymphofollicular hyperplasia. The MG thymus is a reservoir of plasma cells that secrete disease-causing AChR autoantibodies and although thymectomy improves clinical scores, many patients fail to achieve complete stable re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 84 publications
1
39
0
Order By: Relevance
“…Similarly, the thymus in a subset of MG patients includes germinal centers, which are thought to contribute to the generation and maturation of AChR autoantibody producing B cells (3840). Thus, positive selection of N-linked glycosylation DNA motifs may occur in this compartment, and support for this possibility is provided by a previous study where we found that the IgG-switched BCR sequences in MG thymus were enriched N-linked glycosylation DNA motifs (41).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Similarly, the thymus in a subset of MG patients includes germinal centers, which are thought to contribute to the generation and maturation of AChR autoantibody producing B cells (3840). Thus, positive selection of N-linked glycosylation DNA motifs may occur in this compartment, and support for this possibility is provided by a previous study where we found that the IgG-switched BCR sequences in MG thymus were enriched N-linked glycosylation DNA motifs (41).…”
Section: Discussionsupporting
confidence: 67%
“…First, RNA was isolated from frozen peripheral blood mononuclear cells using the RNAEasy Mini kit (Qiagen) per manufacturer’s instructions. Bulk libraries were prepared from RNA using reagents from New England Biolabs as part of the NEBNext® Immune Sequencing Kit as described previously (41, 42). Briefly, cDNA was reverse-transcribed by a template-switch reaction to add a 17-nucleotide unique molecular identifier (UMI) to the 5’ end with streptavidin magnetic bead purification.…”
Section: Methodsmentioning
confidence: 99%
“…Data from Wang et al (2014) 43 were processed in Hoehn et al (2019). 44 Data from Jiang et al (2020b) 45 used only blood samples.…”
Section: Bcr Sequence Datasets and Pre-processingmentioning
confidence: 99%
“…Using a series of state-of-the-art molecular biologic techniques, Jiang et al (8) demonstrate shared B cell receptor repertoires between B cell and plasmablast populations from areas enriched for germinal follicular regions in thymuses of patients undergoing thymectomy (eight patients from the thymectomy trial and one other individual) and the equivalent cell populations in the blood of these same individuals. Both the thymic and blood cells had the characteristics of being antigen-driven.…”
Section: Trafficking Of Cells Between Thymus and The Peripheral Immune Compartment In Mgmentioning
confidence: 99%
“…Jiang et al (8) attempted to see if there were quantitative changes in the presumed thymic origin of peripheral blood cell populations that correlated with clinical response to thymectomy in these same individuals. In the relatively small number of patients in this highly sophisticated immunologic study there was a trend toward correlation between reduced thymus-derived cells in blood sampled at 1 y postthymectomy and the time to clinical improvement, often at 2 y or longer, but it is hard to come to a firm conclusion.…”
Section: Mechanism Of Action Of Thymectomy In Mgmentioning
confidence: 99%